Analisis Dominansi Gulma Invasif Berdasarkan Summed Dominance Ratio (SDR) pada Perkebunan Karet di Gandus, Palembang - Wahyuni, Artika Sri; Huda, Muhammad Komarul; Marisa, Hanifa; Lamin, Syafrina; Jannah, Roudhotul (Mahesa Research Center, 2026)
Invasive weeds possess high adaptability and dispersal capacity, enabling them to alter plant community structure across various agroecosystems, including rubber plantations. This study aimed to identify invasive weed species and analyze their dominance based on the Summed Dominance Ratio (SDR) in a rubber plantation in Gandus Subdistrict, Palembang City. The study employed vegetation analysis using a purposive sampling method with quadrat transects across three observation zones (front, middle, and back of the plantation), each consisting of seven plots measuring 2 × 2 m. Vegetation parameters analyzed included relative density, relative frequency, importance value, and SDR. The results recorded 15 weed species from 8 families with a total of 315 individuals, with Asteraceae representing the most dominant family in terms of species richness. SDR analysis indicated that Rolandra fruticosa was the most dominant species (28.27%), followed by Asystasia gangetica, Digitaria ciliaris, Ageratum conyzoides, and Synedrella nodiflora. The dominance of these species reflects high ecological pressure within the rubber plantation agroecosystem, facilitating the proliferation of invasive weeds. These findings provide baseline information on weed community structure and can serve as a reference for developing more effective weed management strategies in rubber plantations.